2022
DOI: 10.1007/s40620-021-01231-7
|View full text |Cite
|
Sign up to set email alerts
|

How good is a living donor? Systematic review and meta-analysis of the effect of donor demographics on post kidney transplant outcomes

Abstract: Background and Aims Living donor kidneys are considered the best quality organs. In the attempt to expand the donor pool, the donor’s age, sex and body mass index (BMI) might be considered as potential determinants of the kidney transplant outcomes, and thus guide recipient selection. We aimed to investigate the effects of donor demographics on kidney function, graft and recipient survival, delayed graft function (DGF) and acute rejection (AR). Methods Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 55 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…Another factor considered was BMI, which is a conditioning factor for the recovery of renal function, the importance of which lies in the risk of obesity to develop proteinuria and CKD [16,17] . It has been generally agreed on using BMI to evaluate obesity and in any case exclude from donation candidates with a BMI > 35 kg/m 2 , although due to the shortage of donors, some places have agreed to broaden the selection criteria for living donor candidates, without accepting any de nitive limit [16,18] .…”
Section: Discussionmentioning
confidence: 99%
“…Another factor considered was BMI, which is a conditioning factor for the recovery of renal function, the importance of which lies in the risk of obesity to develop proteinuria and CKD [16,17] . It has been generally agreed on using BMI to evaluate obesity and in any case exclude from donation candidates with a BMI > 35 kg/m 2 , although due to the shortage of donors, some places have agreed to broaden the selection criteria for living donor candidates, without accepting any de nitive limit [16,18] .…”
Section: Discussionmentioning
confidence: 99%
“…An interesting finding of our analysis is that donor age, and not donor type, affects the incidence of graft loss. Previous work reports that recipients of grafts from live donors aged < 60 have a 38% lower risk of developing acute rejection compared to those aged > 60 years ( 33 ). Since recipients of older grafts are generally also older in age, this leaves to the open debate on immunosuppression in the elderly, in whom, although physiological immunosenescence linked to biological aging is known, other potential contributors, such as the engraftment of older organs, is associated with higher rejection rates, and thus the need for tailored, age-adopted immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on comparing the outcomes between LRD and LURD transplant recipients. Most studies have shown similar graft survival between recipients of these two types of living donation (5)(6)(7)(8)(9)(10)(11), while some studies have shown a better survival of LRD recipients compared to LURD recipients (12,13). A recent study with 14 370 patients reported similar patient and overall graft survival in LRD and LURD recipients, while a higher death censored graft failure in LURD recipients was noticeable (14).…”
Section: Introductionmentioning
confidence: 99%